Nucleotide sequence of a full-length human endogenous retroviral segment. - Repaske, R (1985)
The nucleotide sequence of a full-length (8.8-kilobase) endogenous C-type human retroviral DNA (clone 4-1) is presented and compared with that of Moloney murine leukemia virus (MoMuLV) DNA. Colinearity of deduced amino acids of clone 4-1 with MoMuLV in the gag and pol regions was clearly evident, and overall amino acid homology in these regions was about 40%. Identification of the putative N terminus of gag and p30, the gag-pol junction, and the C terminus of pol could be established on the basis of sequence homology with MoMuLV. Unique characteristics of the endogenous human retroviral DNA included a tRNA Glu primer binding site separated from the 5' long terminal repeat by a pentanucleotide and a putative env sequence which does not appear to overlap the C terminus of pol and has virtually no homology with the env gene of known infectious retroviruses. Clone 4-1 represents a defective prototype of a human C-type retrovirus which integrated into the germ line some time in the distant past.